Peningkatan Kesadaran Hukum terhadap Pencegahan Pelecehan Seksual di Kalangan Pelajar di MA DDI Padanglampe - Hamzah, Yuli Adha; Mangarengi, Arianty Anggraeny; Reza, Farah Syah; Sapada, Andi Tenri (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Community service activities carried out at Madrasah Aliyah DDI Padanglampe to increase legal awareness regarding the prevention of sexual harassment among students through the Need Assessment method, legal counseling, assistance and evaluation for Madrasah Aliyah DDI Padanglampe students. The purpose of this activity is for students to understand the impact and legal consequences of sexual harassment. For this reason, legal counseling and assistance activities were programmed for Madrasah Aliyah DDI Padanglampe students with the following results; students are able to understand the prevention of sexual harassment and its impact which can have long-lasting effects on victims and perpetrators.